Protective effect of resveratrol on mitochondrial biogenesis during hyperoxia-induced brain injury in neonatal pups - Menghan Yang; Yunchuan Shen; Shuai Zhao; Rong Zhang; Wenbin Dong; Xiaoping Lei (BMC Neuroscience, 2023)
Abstract Background Neonatal hyperoxic brain injury is caused by exposure to hyperphysiological oxygen content during the period of incomplete development of the oxidative stress defence system, resulting in a large number of reactive oxygen species (ROS) and causing damage to brain tissue. Mitochondrial biogenesis refers to the synthesis of new mitochondria from existing mitochondria, mostly through the PGC-1α/Nrfs/TFAM signalling pathway. Resveratrol (Res), a silencing information regulator 2-related enzyme 1 (Sirt1) agonist, has been shown to upregulate the level of Sirt1 and the expression of peroxisome proliferator-activated receptor gamma coactivator-1α (PGC-1α). We speculate that Res has a protective effect on hyperoxia-induced brain injury through mitochondrial biogenesis. Methods Sprague-Dawley (SD) pups were randomly divided into the nonhyperoxia (NN) group, the nonhyperoxia with dimethyl sulfoxide (ND) group, the nonhyperoxia with Res (NR) group, the hyperoxia (HN) group, the hyperoxia with dimethyl sulfoxide (HD) group, and the hyperoxia with Res (HR) group within 12 h after birth. The HN, HD, and HR groups were placed in a high-oxygen environment (80‒85%), and the other three groups were placed in the standard atmosphere. The NR and HR groups were given 60 mg/kg Res every day, the ND and HD groups were given the same dose of dimethyl sulfoxide (DMSO) every day, and the NN and HN groups were given the same dose of normal saline every day. On postnatal day (PN) 1, PN7, and PN14, brain samples were acquired for HE staining to assess pathology, TUNEL to detect apoptosis, and real-time quantitative polymerase chain reaction and immunoblotting to detect the expression levels of Sirt1, PGC-1α, nuclear respiratory factor 1 (Nrf1), nuclear respiratory factor 2 (Nrf2) and mitochondrial transcription factor A (TFAM) in brain tissue. Results Hyperoxia induced brain tissue injury; increased brain tissue apoptosis; inhibited Sirt1, PGC-1α, Nrf1, Nrf2, TFAM mRNA expression in mitochondria; diminished the ND1 copy number and ND4/ND1 ratio; and decreased Sirt1, PGC-1α, Nrf1, Nrf2, and TFAM protein levels in the brain. In contrast, Res reduced brain injury and attenuated brain tissue apoptosis in neonatal pups and increased the levels of the corresponding indices. Conclusion Res has a protective effect on hyperoxia-induced brain injury in neonatal SD pups by upregulating Sirt1 and stimulating the PGC-1α/Nrfs/TFAM signalling pathway for mitochondrial biogenesis.